The Ability of Phytoremediator Mustard (Brassica juncea) to Reduce the Level of Lead (Pb) in Soil - Burhan Muslim (JIK-JURNAL ILMU KESEHATAN, 2018)
Some studies have shown that levels of Pb in the groundwater around the highway positive containing Pb. This study aims to determine the ability of mustard (Brassica juncea) reduce levels of lead in the soil. This research uses experimental pre and post design. The object of this study is Pb in soils with mustard planting treatment to reduce levels of Pb. Implementation research held by making a planting medium that has been contaminated with Pb (NO3) 2. Then in the planting medium mustard planted as many as 10 polybags for a month. Statistical analysis was performed using the t test statistical test to see any significant difference before and seudah Pb planted with mustard. The results showed behwa Brassica juncea has the ability to reduce levels of lead in the growing media in the range of 9.8 to 13.3%. Of  the statistical tests can be concluded that mustard  (Brassica juncea) plants have the ability to significantly reduce levels of Pb contained in the soil.